COMMUNICATION SKILLS BETWEEN EDUCATOR AND PRESCHOOL CHILD AS AN OBJECT OF SOCIALIZATION (International journal of artificial intelligence, 2026)
This article analyzes the role of communication skills between the educator and the preschool child as an object of socialization. The communication process is considered a key tool for children to acquire social norms, develop interaction and cooperation skills, and receive emotional and moral education. The study highlights effective methods for developing communication skills through pedagogical activities, games, and group exercises. The results show that when communication between the educator and the child is systematically and purposefully organized, it enhances children’s social activity and contributes to their personal development.